Circulating monocyte chemoattractant protein‐1 (MCP‐1) is associated with cachexia in treatment‐naïve pancreatic cancer patients. Issue 2 (7th January 2018) - Talbert, Erin E.; Lewis, Heather L.; Farren, Matthew R.; Ramsey, Mitchell L.; Chakedis, Jeffery M.; Rajasekera, Priyani; Haverick, Ericka; Sarna, Angela; Bloomston, Mark; Pawlik, Timothy M.; Zimmers, Teresa A.; Lesinski, Gregory B.; et al.
Abstract: Background: Cancer‐associated wasting, termed cancer cachexia, has a profound effect on the morbidity and mortality of cancer patients but remains difficult to recognize and diagnose. While increases in circulating levels of a number of inflammatory cytokines have been associated with cancer cachexia, these associations were generally made in patients with advanced disease and thus may be associated with disease progression rather than directly with the cachexia syndrome. Thus, we sought to assess potential biomarkers of cancer‐induced cachexia in patients with earlier stages of disease. Methods: A custom multiplex array was used to measure circulating levels of 25 soluble factors from 70 pancreatic cancer patients undergoing attempted tumour resections. A high‐sensitivity multiplex was used for increased sensitivity for nine cytokines. Results: Resectable pancreatic cancer patients with cachexia had low levels of canonical pro‐inflammatory cytokines including interleukin‐6 (IL‐6), interleukin‐1β (IL‐1β), interferon‐γ (IFN‐γ), and tumour necrosis factor (TNF). Even in our more sensitive analysis, these cytokines were not associated with cancer cachexia. Of the 25 circulating factors tested, only monocyte chemoattractant protein‐1 (MCP‐1) was increased in treatment‐naïve cachectic patients compared with weight stable patients and identified as a potential biomarker for cancer cachexia. Although circulating levels of leptin and granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) were found to be decreased in the same cohort of treatment‐naïve cachectic patients, these factors were closely associated with body mass index, limiting their utility as cancer cachexia biomarkers. Conclusions: Unlike in advanced disease, it is possible that cachexia in patients with resectable pancreatic cancer is not associated with high levels of classical markers of systemic inflammation. However, cachectic, treatment‐naïve patients have higher levels of MCP‐1, suggesting that MCP‐1 may be useful as a biomarker of cancer cachexia.